Accountability and ecological sustainability challenges under NPM-based public sector-led urban development: four international comparative cases. Issue 3 (3rd July 2017) - Kuronen, Matti; Heywood, Christopher; Majamaa, Wisa; Weckroth, Mikko
ABSTRACT: This paper compares four different public sector-led urban development institutional arrangements within New Public Management (NPM)'s framework. The cases come from three European countries – Sweden, Finland and the Netherlands – and the Australian state of Victoria. These four jurisdictions, though distant, share much in terms of urban development processes and actors' responsibilities within these processes, as well as legislation concerning urban development. In the comparison, emphasis is placed on addressing public accountability and ecological sustainability. Ecological sustainability is important to the public sector and urban development has a significant role in achieving more ecologically sustainable built environments. It was found out that steering the development projects is relevant to sustainability issues. Accountability needs to be addressed when forming single-purpose organizational arrangements, but the paper concludes that the examined organizations have no flaws in accountability. In examining these cases, it is assumed that all four operate in governance environments dictated by NPM's methods, and their success is thus evaluated in that framework. There is little evidence so far of international comparative urban development research combining values and results achieved; or comparing cases from different jurisdictions.